Working with Schizophrenic People/An Interpretative Phenomenological Analysis from the Aspect of Physiologists - Revis Georgios (2017)
Abstract, Introduction, Methodology, Design, Participants, Data Collection, Data Analysis, Reflexivity, Analysis, Discussion, References, Invitation to Participate, Consent Form, Interview Plan, Debriefing Sheet, Table of Themew, List of Themes and Quotes, Letter of Application.